Advancing the use of scenarios to understand society's capacity to achieve the 1.5 degree target. (May 2019) - Pedde, Simona; Kok, Kasper; Hölscher, Katharina; Frantzeskaki, Niki; Holman, Ian; Dunford, Rob; Smith, Alison; Jäger, Jill
Highlights: We present a framework combining capitals and capacities within SSPxRCP scenarios. Capitals and capacities are needed for society to move towards the 1.5 °C target. Locally derived capitals and capacities complement global mitigation scenarios. Social equality is more important than technological development to achieve the 1.5 °C target. "Business-as-usual" SSP5 has potential only if capitals and capacities are high. Abstract: With a range of potential pathways to a sustainable future compatible with the Paris Agreement 1.5 °C target, scenario analysis has emerged as a key tool in studies of climate change mitigation and adaptation. A wide range of alternative scenarios have been created, and core amongst these are five socio-economic scenarios (Shared Socio-economic Pathways or SSPs) and four emission scenarios (Representative Concentration Pathways or RCPs). Whilst mitigation scenarios (the Shared Policy Assumptions, or SPAs) have been developed for each SSP-RCP combination, describing the actions necessary to match the climate pathway of the RCP, there has not yet been a systematic approach to address whether and how these actions can be enabled in practice. We present a novel and transferable framework to understand society's capacity to achieve the 1.5 °C target, based on four participatory case studies using the SSP-RCP scenarios. The methodology builds on a framework for categorising different types of societal capitals and capacities and assessing their impact on the potential to implement different types of mitigation actions. All four case studies show that SSP1 has the highest potential to reach the target. Although environmental awareness is high in both SSP1 and SSP4, continued social inequalities in SSP4 restrict society's capacity to transform, despite economic growth. In the two least environmentally-aware SSPs, SSP3 and SSP5, the transformation potential is low, but the view on capitals and capacities nonetheless helps identify opportunities for actors to develop and implement mitigation actions. The study highlights that techno-economic assessments of climate strategies need to be complemented by consideration of the critical role played by social and human capital, and by societal capacity to mobilise and create these capitals despite different socio-economic trends. These capitals and capacities are essential to enable the rapid innovation, behavioural change and international co-ordination needed to achieve the 1.5 °C target.